System performance of a residential building using the air-based solar heating system. (1st September 2018) - Choi, Youngjin; Takase, Kozo; Mae, Masayuki
Highlights: A thermal balance of a house using air-based solar heating system is calculated. We propose improvement points of the air-based solar heating system. The change of heat storage effect by foundation-concrete insulation is evaluated. The possibility of a water pack as an additional heat storage material is examined. Abstract: To apprehend the performance of a solar heating system, it is important to first understand the relationship between the heating load and the system elements, such as heat collection, heat storage, and insulation, among others. Due to the fact that the performance of solar heating systems fluctuates with weather conditions, in this study, measurements in three huts were collected at the same time in order to compare the influence by these factors on the system. By installing insulation on concrete, the heat absorption amount of the base concrete was reduced by 13.2% and the heat release amount was increased by 12.0%. This result shows the necessity of insulation in case of using underground space for heat storage in a solar heating system. Also, a possibility of water pack as thermal storage was presented for a solar heating system.